Effects of divalent cations on muscarinic receptor cationic current in smooth muscle from guinea-pig small intestine. - Zholos, A V (1995)
1. Effects of Mg2+ and Ca2+ on muscarinic receptor cationic current (Icat) in guinea-pig ileal smooth muscle cells have been studied using patch-clamp techniques (whole-cell recording). Icat was activated either by externally applied carbachol or, to bypass receptors, by intracellular GTP-gamma-S. 2. Independently of the main permeant cation the current-voltage (I-V) relation for Icat was U-shaped between the reversal potential (usually 0 mV) and very negative potentials such as -120 mV where current could be virtually lost. Adding Ca2+ to Ca(2+)- and Mg(2+)-free external solution reduced inward current and made it less U-shaped whereas adding Mg2+ reduced inward current and shifted more positively the potential at which maximum inward current occurred. 3. Activation of the conductance underlying Icat could be described by the Boltzmann relation which was shifted positively by adding Ca2+ or Mg2+. Extracellular Ca2+ also distorted the relation by increasing the slope factor; maximal conductance was reduced in all cases. Icat relaxation at negative potentials was accelerated by increasing Mg2+ and slowed down by Ca2+. 4. These data suggest the presence of fixed negative surface charges on or near the muscarinic receptor cationic channel, which allow its modulation through alteration of surface potential. Additional more direct ion binding to and blocking of the channel cannot be ruled out. Some additional effects of Ca2+ (if compared with Mg2+) could be explained on the assumption that the Ca(2+)-binding activation site known to be present on the internal side of the channel can be accessible to Ca2+ entering through the open channel during muscarinic receptor stimulation, as Ca2+ ions contribute to a limited extent to Icat. 5. We conclude that voltage-dependent gating of muscarinic receptor cationic channels is an intrinsic channel property and that Ca2+ and Mg2+ have strong modulatory effects.